Storying the Soyacene - Silva, Nathaly Yumi da; Kreysel, Caroline (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2024)
Book ReviewClaiton Marcio da Silva and Claudio de Majo, eds. The Age of the Soybean: An Environmental History of Soy during the Great Acceleration (Winwick: The White Horse Press, 2022).